RANCANG BANGUN GAME STOCK STREET SAGA BERDASARKAN ANALISIS TEKNIKAL - Tristiyanto; Yuliyanto, Kurniawan Dwi; Syarif, Admi; Wulansari, Ossy Endah Dwi (P3M Politeknik Negeri Banjarmasin, 2024)
This research focuses on the development of the